Deconstruction of Bapemperda's Functions in Improving the Effectiveness of Establishing Regional Regulations - Podungge, Abdul Wahab; Hunawa, Robby; Paramata, Adhayani Mentari; Nuna, Muten (JURNAL LEGALITAS, 2022)
This article aims to analyze the function of Bapemperda in increasing the effectiveness of the formation of Regional Regulations in the Bone Bolango Regency. The Regional Regulations Formation Agency (Bapemperda) of the Bone Bolango DPRD is one of the council's equipments for forming regional regulations. The type of research used in this article is empirical normative, which combines a normative legal approach with the addition of various elements of empirical studies. The results show that the implications of political intervention sometimes affect the issues and local regulations issued and do not represent the community's interests but are dominated by political interests. Ideally, local regulations must be responsive and meet usual policy standards that at the implementation level can be used and can answer problems that develop in the community. Human resources have an essential role in an organization, such as the rapid development of information technology, globalization, and changes in the world of positions and work, and are tied to the existing system. Members of Bapemperda and local governments play a role in forming regional regulations and other policy designs. To increase the effectiveness of the formation of Regional Regulations, it is necessary to have a relationship between human resources and the objectives that apply to Bapemperda itself. The researcher then offers a prototype product called CIS-Approach, a development concept from the results of the research and data analysis of the previous authors, which is expected to be a consideration for the government in formulating regional regulatory policies. CIS-Approach indicators are: 1) human resources with the system; 2) human resources with the issue; 3) human resources with regulations.